Protecting Health from Climate Change: Preparedness of Medical Interns - Majra, Jai Pal (Medknow Publications, 2009)
CONTEXT: Climate change is a significant and emerging threat to public health and to meet the challenge, health systems require qualified staff. AIMS: To study the preparedness of medical interns to meet the challenge of protecting health from climate change. SETTINGS AND DESIGN: Medical colleges in a coastal town. Cross-sectional study. MATERIALS AND METHODS: A proportionate number of medical interns from five medical colleges were included in the study. Level of awareness was used as a criterion to judge the preparedness. A self-administered, pretested, open-ended questionnaire was used. Responses were evaluated and graded. STATISTICAL ANALYSIS USED: Proportions, percentage, Chi-test. RESULTS: About 90% of the medical interns were aware of the climate change and human activities that were playing a major role. Ninety-four percent were aware of the direct health impacts due to higher temperature and depletion in ozone concentration, and about 78% of the respondents were aware about the change in frequency / distribution of vector-borne diseases, water borne / related diseases, malnutrition, and health impact of population displacement. Knowledge regarding health protection was limited to mitigation of climate change and training / education. Options like adaptation, establishing / strengthening climate and disease surveillance systems, and health action in emergency were known to only nine (7%), eight (6%), and 17 (13%), respectively. Collegewise difference was statistically insignificant. Extra / co-curricular activities were the major source of knowledge. CONCLUSIONS: Majority of medical interns were aware of the causes and health impacts of climate change, but their knowledge regarding health protection measures was limited.